Uma abordagem de Workflow na capacitação do CERNE1 para a gestão de incubadoras de empresas - Barbosa, Josilan Paulino (2014)
The concept of a business incubator as an innovation and entrepreneurship environment for new companies first occured in the United States, arriving in Brazil in the 80's. This habitat has the role of transforming ideas into succesful businesses. In order to do that, the business incubation process require favorable conditions such as: basic infrastructure to place the projects and high excelence on managing work processes. Based on that need, SEBRAE and ANPROTEC formulated the Centre of Reference for Support Newcoming Businesses – CERNE. CERNE is a work model divided in four levels, that aims to develop 16 managerial processes, including 62 key practices that helps to stablish the maturity of the companies, the incubators, their supporting entities and the continuous improvement of all of them. The deploy of CERNE model in the incubators has been advancing slowly in a way to certify this environment, due to difficulties such as employees turnover, limitation when it comes to external aid, low interaction between incubators and consultants and the lack of document samples to aid the processes managing and the workflow of every step of the deployment. From that scenario comes a proposition to deploy CERNE1 using process and pratices modelling through a Workflow tool, with the workflow editor Together Worflow Editor - TWE, using the XPDL and BPMN bases, aiming to represent graphically the routines and stages of the first level of maturity, helping to built an online course using the MOODLE platform for the audience of business incubators managers and coworkers of the 7 main incubators in Alagoas, to generate interactive learning process and making it possible to systematically and gradually deploy CERNE1.